Influence of prosthesis related factors on the occurrence of early leaflet thrombosis after transcatheter aortic valve implantation. (25th November 2020) - Breitbart, P; Pache, G; Minners, J; Hein, M; Schroefel, H; Neumann, F.-J; Ruile, P
Abstract: Background: Early leaflet thrombosis (LT) is a well described phenomenon after transcatheter aortic valve implantation (TAVI) with an incidence between 10 and 16%. So far, data about predictors of LT are scarce. Purpose: The purpose of the study was to investigate the influence of prosthesis related factors on the occurrence of LT. Methods: Fusion imaging of pre- and post-procedural CTA was performed in 140 TAVI-patients (55 with LT, 85 without LT) to obtain a 3D-reconstruction of the transcatheter heart valve (THV) within the native annulus region. All patients received a balloon-expandable Sapien 3 THV. The length of the THV above and below the native annulus was measured within the fused images to assess the implantation depth. The deployed THV area was quantified on three heights (left ventricular outflow tract end, center of the stent, aortic end) to determine the average expansion of the prosthesis as percent of the nominal area. We also calculated the extent of prosthesis waist in percent of maximum area. The stent tilt was determined in relation to the annulus plane. Results: After multivariate adjustment the extent of THV expansion (odds ratio per 10 percent [CI]: 0.660 [0.555–0.786], P<0.001) and waist (odds ratio per 10 percent [CI]: 0.725 [0.615–0.854], P<0.001) had significant, independent influence on the occurrence of LT. Neither the implantation depth nor the stent tilt showed any influence on LT manifestation (P=0.393 and 0.578). Conclusion: Our study suggests that less than fully expanded Sapien 3 THVs are more prone to LT, whereas some degree of waist was protective. These deployment characteristics may help identify patients who qualify for intensified surveillance. Funding Acknowledgement: Type of funding source: None